Stoic romanticism and the ethics of emotion. - Risinger, Jacob (Princeton : Princeton University Press, 2021)
"At first glance, Stoic philosophers and Romantic writers seem to have nothing in common: the ancient Stoics championed the elimination of emotion, and Romantic writers made a bold new case for its expression, adopting "powerful feeling" as the bedrock of poetry itself. In fact, as this book argues, classical Stoicism had a substantial influence on Romantic literary culture. Many Romantic writers, invested in identifying emotion as the origin of art, also demonstrated interest in the Stoic idea that aesthetic and ethical judgment demanded the transcendence of emotion. Stoicism, the author argues, was a central preoccupation in a world newly destabilized by the French Revolution. In creating a space for the skeptical evaluation of feeling and affect, Stoicism in the Romantic period became the subject of poetic reflection, ethical inquiry, and political debate for such writers as Wordsworth, Coleridge, Byron, Mary Shelley, and Ralph Waldo Emerson"--
Cover -- Contents -- Acknowledgments -- List of Abbreviations -- Introduction -- Chapter 1. Stoic Moral Sentimentalism from Shaftesbury to Wollstonecraft -- Chapter 2. Wordsworth and Godwin in "Frozen Regions" -- Chapter 3. Coleridge, Lyric Askesis, and Living Form -- Chapter 4. The True Social Art: Byron and the Character of Stoicism -- Chapter 5. Stoic Futurity in Sarah Scott and Mary Shelley -- Chapter 6. Emerson, Stoic Cosmopolitanism, and the Conduct of Life -- Notes -- Bibliography -- Index
JSTOR
Keywords: English literature -- 19th century -- History and criticism; Romanticism; Stoics in literature; Littérature anglaise -- 19e siècle -- Histoire et critique; Romantisme; Stoïcisme dans la littérature.; romanticism (form of expression); LITERARY CRITICISM / Ancient & Classical; English literature; Romanticism; Stoics in literature; 1800-1899; A Vindication of the Rights of Men; Aesthetics; Altruism; An Essay on Man; Anacharsis; Anecdote; Antipathy; Antithesis; Apatheia; Apathy; Asceticism; Bellum omnium contra omnes; Byronic hero; Character of the Happy Warrior; Classical language; Confidant; Contingency (philosophy).; Cosmopolitanism; Critical and Historical Essays (Macaulay).; Criticism; Critique; David Hume; Defamiliarization; Delusion; Descriptive poetry; Disenchantment; Effeminacy; Emotional detachment; Equanimity; Ethics; Expressivism; Falsity; Fatalism; Fears in Solitude; Gentlewoman; Historicism; Houyhnhnm; Hypocrisy; Idealism; Idealization; Impartiality; Inductive reasoning; Indulgence; Intentionality; Invective; Irony; Lord Byron; Lyrical Ballads